MENJADI MANUSIA KREATIF: Sudut Pandang Psikologi Islami - Nashori, Fuad (HUMANITAS (Jurnal Psikologi Indonesia), 2004)
AbstractThis writing intended to reveal Islamic Psichology view to creativity. Islamic Psichology it selfmeans a study about human soul and behaviour based on Islamic world view. Islamic Psichology bas aview that religiousness gives impact to crativity. Fervent belief, diligent worship, charities and farventreligious experince are proved anable man to get creative idea that has bigher or more eternal truth level.Creativity certainly gives impact to the glory of  Islamic society.Keyword : Creativity islamic psichology